Colonic leiomyoma. Pseudoapendicular presentation. - Estrugo, Roberto; Ruso, Luis; de Stefanis, Eduardo (Cirugía del Uruguay, 1989)
Authors present a case of ascending colon leiomyoma whose clinico-echographical presentation resembled that of an appendicular abscess. They examine data on the subject and point out these tumours'low incidence.